Protéger et guérir : la mission du gouvernement et des associations d’aide aux détenues en Angleterre entre 1856 et 1914 - Alice Bonzom (Cahiers Victoriens et Edouardiens)
Mary Carpenter, a Victorian prison reformer, asserted that women prisoners were a threat to society, even more so than their masculine counterparts. In Victorian and Edwardian England, life after release from prison was fraught with hurdles, especially for women. Female criminals had deviated from normative gender-biased ideologies describing woman’s true nature as meek, gentle, modest and shameful; they were stigmatized and ostracized, even after serving their sentences in a local or a convict prison. In 1856, Joshua Jebb, Chairman of Convict Prisons, decided to commit to the cause of these women by opening a special refuge, a ‘home’ designed to save them by teaching them ‘womanly qualities’. However, the refuge was quickly stigmatised and became a prison. Yet, this governmental failure paved the way for the efforts of women reformers, who saw the redemption of their ‘fallen’ sisters as their duty. They set up philanthropic societies, opened ‘homes’ and visiting societies to lead criminals to atonement. The idealized views of womanhood, the prescriptive social roles and the contemporary fears for traditional values which shaped the female criminal system also fashioned the missionary work that surrounded the penal sphere. In a sense, lady visitors were missionaries upholding the values and projects of the Empire. But their efforts led to female empowerment: reformers played an active part in the management of relief societies, challenging their traditionally domestic positions. They also faced obstacles, embodied by people who believed that guilty deviants were being unfairly ‘pampered’. The study of this counter-commitment, as well as the struggle of charitable societies and some government officials reveals a facet of the way in which criminals were perceived by society, while the philanthropic network became a net in which some women were ensnared.